2022
DOI: 10.1242/jeb.243559
|View full text |Cite
|
Sign up to set email alerts
|

Paths towards greater consensus building in experimental biology

Abstract: In a recent editorial, the Editors-in-Chief of Journal of Experimental Biology argued that consensus building, data sharing, and better integration across disciplines are needed to address the urgent scientific challenges posed by climate change. We agree and expand on the importance of cross-disciplinary integration and transparency to improve consensus building and advance climate change research in experimental biology. We investigated reproducible research practices in experimental biology through a review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 136 publications
(162 reference statements)
0
20
0
Order By: Relevance
“…The challenge of finding and accessing research data is not unique to the microplastics research community. Similar patterns in data sharing practices are common in well-established disciplines such as social sciences, water resources, lowtemperature geochemistry, ecology, and health sciences (Stagge et al, 2019;Brantley et al, 2021;Tedersoo et al, 2021;Roche et al, 2022b). For example, Stagge et al (2019) assessed data availability and research reproducibility in hydrology and water resources across several journals and found that, while approximately 70% of the sampled articles stated some materials were available, only around 48% of the materials could be accessed online.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The challenge of finding and accessing research data is not unique to the microplastics research community. Similar patterns in data sharing practices are common in well-established disciplines such as social sciences, water resources, lowtemperature geochemistry, ecology, and health sciences (Stagge et al, 2019;Brantley et al, 2021;Tedersoo et al, 2021;Roche et al, 2022b). For example, Stagge et al (2019) assessed data availability and research reproducibility in hydrology and water resources across several journals and found that, while approximately 70% of the sampled articles stated some materials were available, only around 48% of the materials could be accessed online.…”
Section: Discussionmentioning
confidence: 77%
“…For example, Stagge et al (2019) assessed data availability and research reproducibility in hydrology and water resources across several journals and found that, while approximately 70% of the sampled articles stated some materials were available, only around 48% of the materials could be accessed online. In experimental biology, only one in five papers (21.5%) included a data sharing statement or associated open data (Roche et al, 2022b). An overview of published research funded by the Canadian Institutes of Health Research (CIHR) (Government of Canada, 2021), a federal funding agency which has an explicit data sharing expectation, showed that for a subset of CIHR funded projects, only 45.2% of studies had readily accessible data (Read et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open data and improved transparency make it possible to scrutinize other researchers’ data ( Roche et al ., 2022 ). Conservation Physiology embraces the spirit of the FAIR principles (see https://www.go-fair.org/fair-principles/ ) whereby data (and code) associated with papers are findable, accessible, interoperable and repeatable.…”
Section: Encouraging Ethical Behaviour and Building Integritymentioning
confidence: 99%
“…Now, 20% of journals publishing research in E&E mandate open data [17]. Strong journal policies are effective at ensuring that more datasets are shared [18][19][20], which is often touted as a win for open science [21]. Yet, problems persist [19,22,23].…”
Section: Introductionmentioning
confidence: 99%